Implementasi Model Pembelajaran Project Based Learning dalam Meningkatkan Karakter dan Pemahaman Konsep Materi Indahnya Kebersamaan pada Siswa Kelas IV SDN Kuala Batee - Raihan Riska; Rambang Muharramsyah; Cut Khairani (LPPM Institut Pendidikan Nusantara Global, 2026)
This research aims to determine the implementation of the Project Based Learning (PjBL) model in improving students’ character and conceptual understanding of the material Indahnya Kebersamaan (The Beauty of Togetherness), as well as the effectiveness of the Project Based Learning model compared to conventional teaching methods in Grade IV of SDN Kuala Batee. The research method used in this study is Classroom Action Research (CAR) with SWOT analysis. The subjects of this research were 25 fourth-grade students of SDN Kuala Batee, consisting of 15 female students and 10 male students. Data collection techniques included tests, observation, and documentation. Based on the results of the study, it can be concluded that Project Based Learning is able to improve students’ character as well as their conceptual understanding of the material Indahnya Kebersamaan. Through project-based activities, students demonstrated significant development in cooperation, responsibility, tolerance, and the courage to express opinions. Collaborative activities such as group discussions, poster creation, and presentations encouraged students to be more active, confident, and positively engaged with their peers. In addition, students' conceptual understanding strengthened, as evidenced by the increase in learning mastery from meeting I to meeting IV, ultimately reaching 100%. The Project Based Learning model is more effective than conventional teaching methods in Grade IV of SDN Kuala Batee. This effectiveness is seen from the significant improvement in learning mastery, the shift from passive to active student participation, and the increasingly conducive and structured classroom environment. Students appeared more enthusiastic and directly involved in the learning process because PBL allowed them to experience, create, and collaborate in completing various projects.